2017
DOI: 10.1021/acs.est.6b03950
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Scale Microbial Food Chain To Study Bioaccumulation, Biomagnification, and Ecotoxicity of Cadmium Telluride Quantum Dots

Abstract: The increasing applications of engineered nanomaterials (ENMs) in consumer products warrant a careful evaluation of their trophic transfer and consequent ecological impact. In the present study, a laboratory scale aquatic microbial food chain was established using bacteria (Escherichia coli (E. coli)) as a prey and ciliated protozoan (Paramecium caudatum) as a predator organism to determine the impact of cadmium telluride quantum dots (CdTe QDs). We observed that 29% of bacterivory potential of paramecium was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 66 publications
0
16
0
1
Order By: Relevance
“…Cadmium telluride quantum dots (CdTe QDs) caused abnormal foraging behavior (related to the altered function of the motor neurons) in C. elegans, at long-term early onset exposure. Thus, a decrease in fluorescence of the motor neurons cell bodies was observed, indicating an alteration in [148]).…”
Section: Cadmium Nanomaterialsmentioning
confidence: 94%
See 2 more Smart Citations
“…Cadmium telluride quantum dots (CdTe QDs) caused abnormal foraging behavior (related to the altered function of the motor neurons) in C. elegans, at long-term early onset exposure. Thus, a decrease in fluorescence of the motor neurons cell bodies was observed, indicating an alteration in [148]).…”
Section: Cadmium Nanomaterialsmentioning
confidence: 94%
“…It was observed that the QDs caused the loss of the bacterivory potential of paramecium, including an 12 h delay in doubling time. When paramecium was exposed to the QDs (25 mg/L at 24 h), these NMs were bioaccumulated, as shown by the fluorescence based stoichiometric analysis ( Figure 31) [148]. [148]).…”
Section: Cadmium Nanomaterialsmentioning
confidence: 96%
See 1 more Smart Citation
“…QD can dissolve in water to release toxic Cd 2 + ions and the CdTe QD bioaccumulate over several trophic levels. [131] Lead is a known environmental toxicant that, because of substantial human use, has had a strong negative impact on human health. Historically, lead has been used in various consumer products, [132] and over time, corrosion forms water-soluble lead compounds that end up in the environment contaminating drinking water reserves or getting taken up by plants.…”
Section: Public Exposurementioning
confidence: 99%
“…As a result, the use of highly toxic and hazardous materials, such as paint and solvents, has been gradually increasing. 16,17 Due to the small size and limited resources of these auto body and auto repair shops, hazardous substances are often mishandled and improperly disposed of into the environment. 18,19 Moreover, controversy has arisen over the regulation of these businesses, which concerns not only the condition of the surrounding environment, but the health and safety of workers as well.…”
Section: Introductionmentioning
confidence: 99%